Discovery of a novel class of potent and selective tetrahydroindazole-based sigma-1 receptor ligands. Issue 9 (1st May 2019) - Iyamu, Iredia D.; Lv, Wei; Malik, Neha; Mishra, Rama K.; Schiltz, Gary E.
Graphical abstract: Abstract: The sigma-1 and sigma-2 receptors have been shown to play important roles in CNS diseases, cancer, and other disorders. These findings suggest that targeting these proteins with small-molecule modulators may be of important therapeutic value. Here we report the development of a new class of tetrahydroindazoles that are highly potent and selective ligands for sigma-1. Molecular modeling was used to rationalize the observed structure-activity relationships and identify key interactions responsible for increased potency of the optimized compounds. Assays for solubility and microsomal stability showed this series possesses favorable characteristics and is amenable to further therapeutic development. The compounds described herein will be useful in the development of new chemical probes for sigma-1 and to aid in future work therapeutically targeting this protein.